Understanding Carotenoid Dynamics via the Vibronic Energy Relaxation Approach - Šebelík, Václav; Duffy, Christopher D P; Keil, Erika; Polívka, Tomáš; Hauer, Jürgen (The journal of physical chemistry. B, 2022)
Carotenoids are an integral part of natural photosynthetic complexes, with tasks ranging from light harvesting to photoprotection. Their underlying energy deactivation network of optically dark and bright excited states is extremely efficient: after excitation of light with up to 2.5 eV of photon energy, the system relaxes back to ground state on a time scale of a few picoseconds. In this article, we summarize how a model based on the vibrational energy relaxation approach (VERA) explains the main characteristics of relaxation dynamics after one-photon excitation with special emphasis on the so-called S* state. Lineshapes after two-photon excitation are beyond the current model of VERA. We outline this future line of research in our article. In terms of experimental method development, we discuss which techniques are needed to better describe energy dissipation effects in carotenoids and within the first solvation shell.
Keywords: Light-Harvesting Protein Complexes; světlosběrné proteinové komplexy; Carotenoids; Vibration; fotosyntetická reakční centra (proteinové komplexy); fotony; Photons; karotenoidy; Photosynthetic Reaction Center Complex Proteins; vibrace